Depression : the way out of your prison - Rowe, Dorothy (Routledge, 1996)
Depression is the experience of a terrible isolation, of being alone in a prison. But by understanding how we build the prison of depression we can dismantle it for ever. Dorothy Rowe gives us a way of understanding depression, allowing us to take charge of our lives. She shows it is not an illness requiring drugs but a defence we use to hold ourselves together when we feel our lives falling apart. This bestselling book, now in its second edition, contains the stories of people who have left the prison of depression and changed their lives for ever.